2016
DOI: 10.1016/j.gene.2016.02.019
|View full text |Cite
|
Sign up to set email alerts
|

SALL4, the missing link between stem cells, development and cancer

Abstract: There is a growing body of evidence supporting that cancer cells share many similarities with embryonic stem cells (ESCs). For example, aggressive cancers and ESCs share a common gene expression signature that includes hundreds of genes. Since ESC genes are not present in most adult tissues, they could be ideal candidate targets for cancer-specific diagnosis and treatment. This is an exciting cancer-targeting model. The major hurdle to test this model is to identify the key factors/pathway(s) within ESCs that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
93
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 145 publications
(211 reference statements)
1
93
0
Order By: Relevance
“…30 In AML, SALL4 directly interacts with β-catenin and induces the activation of Wnt/β-catenin signalling pathway, leading to the upregulation of the target genes of Wnt/β-catenin pathway including cyclin D1 and c-Myc. 7 CD44 is also suggested as a downstream target gene of Wnt/β-catenin signalling.…”
Section: Discussionmentioning
confidence: 99%
“…30 In AML, SALL4 directly interacts with β-catenin and induces the activation of Wnt/β-catenin signalling pathway, leading to the upregulation of the target genes of Wnt/β-catenin pathway including cyclin D1 and c-Myc. 7 CD44 is also suggested as a downstream target gene of Wnt/β-catenin signalling.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor Sal‐like protein 4 (SALL4) is highly expressed in primordial germ cells, germ cells, early embryos, and embryonic stem cells (ESCs). It is critically involved in the self‐renewal and maintenance of pluripotency in ESCs 5 . Yuri, et al 6 demonstrated that SALL4 may be crucial for the lineage commitment in the inner cell mass cells and trophectoderm.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to clarify the relationship between SALL4 and some of these factors would help to understand mechanisms that control the self-renewal and differentiation of piPSCs. Sall4 is vital for the maintenance of an undifferentiated state in both human and mouse ESCs [13] . Chromatin immunoprecipitation (ChIP) assays indicate that Sall4 binds to multiple loci in the genome, suggesting that Sall4 is a guardian of pluripotency that regulates many genes [7,11,14] .…”
Section: Introductionmentioning
confidence: 99%